Penser l'humain et la technique Simondon et Derrida après la métaphysique - Alombert, Anne (La croisée des chemins, 2023)
Gilbert Simondon's and Jacques Derrida's works have never been studied jointly, even though the two authors shared a historical context, a theoretical background and a set of common problems typical of the 1960's. This book suggests to go beyond this lack through a confrontation of their thoughts around three major questions: the question of metaphysics and the relationship between philosophy and science; the question of humanity and the relationship between life and consciousness; the question of technology and the relationship between memory and archives. This articulation of Simondon's and Derrida's reflections shows that it is possible to overcome traditional oppositions between animality and humanity, nature and culture or nature and technique. This philosophical gesture enables us to think the relationship between life, technique and spirit outside of dualist metaphysics, as well as to understand the anthropological issues of contemporary technological transformations. Such an understanding has become necessary in order to face the challenges of Anthropocene and transhumanism.